2017
DOI: 10.22214/ijraset.2017.10219
|View full text |Cite
|
Sign up to set email alerts
|

Review on Implementation of Kaizen Technique for Productivity Improvement in Manufacturing Organization

Abstract: -The aim of this paper is to study and idea aboutKaizen technique for a small improvement in a manufacturing company. The paper describes basis definition of Kaizen philosophy & a review on Kaizen concept and its implementation. Kaizen is one of the most important technique of continuous improvement. This paper explains various literature and presents a concept of Kaizen, which useful fornew research in another field. Kaizen is an approach focused on improving productivity, reducing variation and eliminating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Son yıllarda küçük ve orta ölçekli firmalarda ekipman etkinliğinin iyileştirilmesi üzerine olan çalışmalarda farklı sonuçlar elde edilmektedir. Örneğin, tekstil sektöründe deri işleme makinelerinde bulunan TEE değerlerinin üretim öncesinde yapılan iyileştirmeler ile %5 oranında arttırabileceği bulunmuştur (Patel ve Deshpande, 2016). İstanbul'da küçük işletmeli bir ahşap kapı üretim hattında TEE yaklaşımı ekipman iyileştirmesinde kullanılmıştır.…”
Section: Li̇teratür Taramasiunclassified
“…Son yıllarda küçük ve orta ölçekli firmalarda ekipman etkinliğinin iyileştirilmesi üzerine olan çalışmalarda farklı sonuçlar elde edilmektedir. Örneğin, tekstil sektöründe deri işleme makinelerinde bulunan TEE değerlerinin üretim öncesinde yapılan iyileştirmeler ile %5 oranında arttırabileceği bulunmuştur (Patel ve Deshpande, 2016). İstanbul'da küçük işletmeli bir ahşap kapı üretim hattında TEE yaklaşımı ekipman iyileştirmesinde kullanılmıştır.…”
Section: Li̇teratür Taramasiunclassified
“…Typically, PDCA cycles are used in the manufacturing industry to minimise waste of time when implementing changes. A cycle consists of four major stages, which are as follows [9]:…”
Section: The Deming Cyclementioning
confidence: 99%
“…Patel & Patange indicated that reducing and eliminating losses, improving guidance time, better use of space, better results in a production line are the key results of Kaizen's implementation. Several studies show that Kaizen tools are very effective in all companies for improving the process and waste reduction (Patel, 2017). Raeisi et al (2009) from the establishment of a Kaizen model for improving the process in the Tehran Polytechnic Polyclinic Laboratory concluded that the establishment of the operational Kaizen model would improve the performance indicators of the processes, reduce costs, eliminate losses, make optimal use of resources, and also implement the dressing system in The laboratory has been studied (Raeisi et al, 2009).…”
Section: Hypothesismentioning
confidence: 99%